Republic of San Marino : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2016)
This paper offers elements of a possible strategy to deal with San Marino's nonperforming loans (NPLs). It provides a brief overview of the reasons behind the accumulation of impaired assets by Sammarinese banks. This paper also presents some stylized facts regarding the nature and composition of San Marino's problem loans. Further, it summarizes the experience of other small economies in dealing with weak banks and NPLs, with a view to drawing policy lessons. This paper also discusses recent measures implemented by the Sammarinese authorities to address weak financial institutions and their problem assets and examines the main impediments to deal with NPLs in San Marino's legal and tax framework.